New insights into the evaluation criteria for high-quality deep marine shale gas reservoirs in the Longmaxi formation: Evidence from organic matter pore development characteristics - Zhu, Boyuan; Meng, Jianghui; Pan, Renfang; Hu, Haiyan; Song, Chen; Zhu, Zhengping; Jin, Jineng (Frontiers in Ecology and Evolution, 2023)
Porosity, total organic carbon content, brittle mineral content, and gas content are now the primary references for classifying and evaluating marine shale gas reservoirs in China. Is there a more effective and appropriate reservoir classification scheme for deep marine shale? The Longmaxi Formation in Luzhou, southern Sichuan Basin, China, is the main object of study. Quantitative analysis and modeling using data from field emission scanning electron microscopy, nitrogen adsorption, and logging were used to characterize organic matter (OM) pore multi-scale development and reveal the relationship between OM pore and the high-quality reservoirs. Microscopic and macroscopic indications from OM pores show that a large number of OM pores were developed in high-quality reservoirs. OM surface porosity occupancy of the high-quality reservoir in the Luzhou area was more than 60%. OM porosity occupancy was more than 50%. The nitrogen adsorption-desorption hysteresis loops demonstrate the development of bottleneck and wedge-shaped OM pores. Characterization of multi-scale pore structure by box dimension, pore volume and specific surface area. It is found that the key to the formation of high-quality reservoirs was the massive development of OM mesopores in siliceous shale and the relatively homogeneity structure, which was conducive to the enrichment and migration of shale gas. Furthermore, the improved model decreased the relative error in predicting the OM porosity by about 32.5%. The use of OM porosity occupancy for high-quality reservoir classification was better, and the results were consistent with geological understanding. OM porosity occupancy showed that the area from Lunanxi to Luzhou to Rongchang to Jiangjin was the key exploration area for high-quality reservoirs in southern Sichuan. This study is expected to provide a new idea for OM pore modeling analysis and deep marine shale gas reservoir classification.